The dark wild - Torday, Piers, 1974- (Viking, an imprint of Penguin Group (USA) LLC, 2015)
"After gathering together the Last Wild, the last animals still alive, Kester Jaynes is faced with a new task--facing the Dark Wild, the animals who live underground and want to destroy humankind"--